Peningkatan Keamanan dan Efisiensi Koneksi Jaringan Antar Cabang Dengan Menggunakan CISCO Software-Defined Wan (SD-WAN) (Studi Kasus : BANK XYZ) - Febryo Ponco Sulistyo (FORMAT, 2023)
Software Defined WAN or better known as SDWAN has now become a technology that is hype and has a lot of interest, in addition to simplifying SDWAN operations, it can also reduce operational costs, especially links. Researchers will make it within the scope of the PoC Lab (Proof of Concept) so that later the results from this PoC can show the expected results, namely being able to improve the security of connections between branches and the results achieved by devices between branches whose connections are successful using SD-WAN with traffic and data that already encrypted with IPSEC and also other features by the Cisco SDWAN